A programmed cell division delay preserves genome integrity during natural genetic transformation in Streptococcus pneumoniae - Matthieu J. Bergé (Nature Portfolio, 2017)
In Streptococcus pneumoniae, competence for genetic transformation is accompanied by a pause in growth. Here, Bergé et al. show that this pause is linked to the cell cycle via at least two pathways that impair peptidoglycan synthesis and preserve genomic integrity during transformation.